The Sufi Personality of Ma‘r?f al-Karkh? and His Role in Sufism's Origin - Eraslan, Soner (Fırat University, 2022)
The problem of the origin of religious sciences has been discussed by both Islamic scholars and orientalists from sectarian, cultural, social and many different aspects. Sufism is one of the main sciences that are the subject of these discussions in terms of its source. Some Western researchers; they regarded the religion of Islam as inadequate in the face of the complexity of sufism. They claimed that the science of sufism was inspired by different religions and traditions such as Christianity Gnosticism, Buddhism, Persian and Indian. Another discussion on the origin problem of sufism is that it is of Shia origin. Some early sufis have been scrutinized on the aforementioned issues due to their social environment and teachings. The scope of the study will be created specifically for Ma‘r?f al-Karkh? (d. 200/815). The relevant issue will be evaluated from this aspect. Because Ma'rûf attracts attention as an extremely important sufi because he is at the center of the science of sufism. As a matter of fact, Sar? al-Saqa??, who is the first person to mention states and authorities in the records, states that he acquired all his knowledge through Ma'rûf. Sar?, on the other hand, influenced Junayd because he was the uncle and teacher of Junayd, known as "seyyidü't-taife". Therefore, the life and teachings of Ma'rûf have spread to the foundation of sufism. Besides, it has made him a shareholder in the formation of the theoretical background of sufism. Ma'rûf's reconciliation of Sufism with truths can be considered as an example. The subject of the article is the sufi life of Ma‘r?f al-Karkh?, who is at the center of these discussions, and his role in the origin of sufism because his family is a member of the Sâbiî or Christianity religion and he is a Muslim at the hands of Imam Al? al-Ri?? (d. 203/819). Ma'rûf is in contact with other religions because of his family. In addition, he is in close contact with Al? al-Ri?? in the chain of isnad, which includes seven imams, whom Shiite circles call "golden circle". Therefore, the fact that he is one of the leading figures in the history of sufism increases the importance of the subject in his eyes. Therefore, while the life of Ma'rûf will be examined through the history of sufism, the history of sufism will be mentioned from the specificity of Ma'rûf. Because, in contrast to the normative sciences, the sufi field is dominated by the experiences and teachings of the sufis.

Bu çalışmanın konusu, bazı İslâm âlimleri ve oryantalistler tarafından tartışılagelen tasavvuf ilminin menşei probleminin Ma‘rûf el-Kerhî özelinde değerlendirilmesidir. Reynold A. Nicholson gibi oryantalistlerin bir kısmı tasavvufun giriftliği karşısında İslâm dinini yetersiz görmüş, bu ilim dalının Hristiyanlık Gnostisizmi, Budizm, Fars ve Hint gibi farklı din ve geleneklerden mülhem olduğunu iddia etmiştir. Kimi düşünürler ise tasavvuf ilminin menşeini Şiîlik çerçevesinde tartışmışlardır. Zira Ma‘rûf’un ailesinin farklı bir dine mensup olması ve kendisinin İmam Ali er-Rızâ elinden Müslüman olması onu bu tartışmaların merkezine sevk etmiştir. Çalışmanın amacı Ma‘rûf özelinde tasavvufun menşei hususunda serdedilen görüşlerin değerlendirilip erken ve klasik dönem sûfî literatürü ışığında tetkik edilmesidir. Çalışmanın kapsamı ise Ma‘rûf hakkında erken ve klasik dönem sûfî literatüründe nakledilen fragmanlar ve bazı İslâm âlimleri ve oryantalistlerin konu hakkındaki savları ile sınırlandırılmıştır.
Ma‘rûf el-Kerhî'nin Sûfî Şahsiyeti ve Tasavvufun Menşeindeki Rolü
Keywords: Religious Studies; Din Araştırmaları